2015
DOI: 10.1038/ncomms9026
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical forces regulate the interactions of fibronectin and collagen I in extracellular matrix

Abstract: Despite the crucial role of extracellular matrix (ECM) in directing cell fate in healthy and diseased tissues—particularly in development, wound healing, tissue regeneration and cancer—the mechanisms that direct the assembly and regulate hierarchical architectures of ECM are poorly understood. Collagen I matrix assembly in vivo requires active fibronectin (Fn) fibrillogenesis by cells. Here we exploit Fn-FRET probes as mechanical strain sensors and demonstrate that collagen I fibers preferentially co-localize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
244
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 277 publications
(276 citation statements)
references
References 68 publications
15
244
0
3
Order By: Relevance
“…2D). Consistent with this notion, imaging studies employing fluorescence probes as an indicator of strain exerted on FN fibrils indicate that collagen associates preferentially with relaxed fibrils, as freshly elaborated FN fibrils are known to be (Kubow et al, 2015)…”
Section: Binding Of Plasma Fn To Collagenmentioning
confidence: 72%
“…2D). Consistent with this notion, imaging studies employing fluorescence probes as an indicator of strain exerted on FN fibrils indicate that collagen associates preferentially with relaxed fibrils, as freshly elaborated FN fibrils are known to be (Kubow et al, 2015)…”
Section: Binding Of Plasma Fn To Collagenmentioning
confidence: 72%
“…The schematic summary of the sequential deposition of tissue components during growth given in figure 5b, is reminiscent of the geometrical model proposed to describe the organization of tensile cells on a curved surface [44], and indicates a transfer of this same organization to the fibrous components of the ECM as previously suggested [45]. It has been shown that collagen can self-organize into highly aligned, chiral and cholesteric liquid crystal-like structures in a completely cell-free system [66][67][68][69], while it can only be assembled in cell culture in the presence of fibronectin [65]. Our results on the coalignment of collagen with previously deposited cells and fibronectin, and on the importance of cellular tension for ECM organization, emphasize the importance of active cellular control over such self-organizing processes.…”
Section: Discussionmentioning
confidence: 97%
“…Collagen I (Col I) is another prominent ECM protein with multiple contributions to tumorigenesis [7,8]. Col I deposition is primarily dependent on previously assembled Fn matrices [912]. Therefore, assessing how Fn-Col I interactions are altered during tumorigenesis is critical to our understanding of tumor stroma modifications that mediate invasive tumor growth.…”
Section: Introductionmentioning
confidence: 99%